Fonologia e alfabetização: efeitos de um programa de intervenção para recuperação de alunos do 5º ano do Ensino Fundamental com atrasos na aprendizagem da linguagem escrita - Carvalho, Dayse Karoline Sousa Silva de (2012)
The cognitive psychology has contributed much to the development of scientific knowledge about learning the written language. Pedagogical intervention programs demonstrate positive results in reading and writing with the use of procedures to develop phonological awareness, stimulating the individual's perception to the phonological structure of the language in question. With bases these assumptions, the present study investigated the effects of an intervention program aimed at the systematic teaching of written language, based on phonology, students in 5th grade elementary school that show delays in learning to read and write. The research was conducted in a public school, located in Greater São Paulo. The study sample of 19 children and women, divided into two groups: the intervention group with 11 children aged 9 to 13 years and the control group aged 10 to 12 years. The research was conducted in three phases: pre-test, intervention and post-test. We used tests of reading and writing words and phrases of words and phrases. The intervention program consisted of games and activities aimed at developing the skills of reading and writing, considering the phonological aspects of language. It was developed by the researcher with the participants in the intervention group, four times a week, 28 sessions of activities, each lasting from 3:30 am, with two breaks of 15 minutes each. At the end of the intervention was carried out the post-test. The results of the tests applied in both situations assessment (pretest and posttest) were presented to groups of intervention and control, as scores (raw and percentage). The raw scores were converted into percentages in order to verify the existence of differences between the two stages of research, before and after the intervention. Results showed positive effects of the intervention on the performance of participants in the intervention group, both in the skills of reading and writing words. The results show the effectiveness of pedagogical strategy used, based on phonology, to improve the ability to read and write